Risk factors for mortality among Human Immuno Virus infected children on antiretroviral therapy - Bule, Sunil; Wade, Minal (International Journal of Contemporary Pediatrics, 2019)
Background: Children infected with HIV often reach the health care well after progression to severe immunosuppression which results in higher morbidity and mortality as compared to adults. They are vulnerable to faster disease progression compounded by susceptibility infections and social factors like attrition of caretakers. The present study delineates the factors for poor outcomes among HIV infected children. Methods: The records of HIV infected children from 1 to 15 years of age, started on HAART, registered at ART Centre at a tertiary hospital were reviewed in the Retrospective descriptive study. The demographic details, growth parameters, clinical features, WHO staging and investigations were assessed to study the risk factors for mortality in these children. Results: Amongst the 205 HIV infected children, enrolled in the study, the incidence of mortality was 27/205 (13.7%). The mean age of HIV infected children on ART in the no mortality and mortality group was 8.19 years and 8.25 years. The mean WHO stage of HIV infected children on ART in no mortality and mortality groups at the start of the study was 2.75 (SD=0.89) and 3.66 (SD=0.48), respectively. The mean CD4 count at start in the mortality group (195.85±105.57 cells/mm3) is significantly lower as compared to the no mortality group (306.2+355.66 cells/mm3). The mean grade of malnutrition in the no mortality and mortality groups was 1.84 and 2.88, respectively. Tuberculosis was present in 48.78% at start. Conclusions: Presence of advanced clinical stage, immunosuppression, poor nutritional state, and shorter duration of therapy are important factors deciding outcome of the children on HAART. The intense monitoring in period post starting of HAART will ensure better outcomes.